Disrupted-in-schizophrenia-1 SNPs and susceptibility to schizophrenia: evidence from Malaysia - A. Talib, Norlelawati; Abdullah, Kartini; Ku Zaifah, Norsidah; Musa, Ramli; Abdul Razak, Tariq; Wan Rohani, Wan Taib (Korean Neuropsychiatric Association, 2015)
Even though the role of the DICS1 gene as a risk factor for schizophrenia is still unclear, there is substantial evidence from functional and cell biology studies that supports the connection of the gene with schizophrenia. The studies associating the DISC1 gene with schizophrenia in Asian populations are limited to East-Asian populations. Our study examined several DISC1 markers of schizophrenia that were identified in the Caucasian and East-Asian populations in Malaysia and assessed the role of rs2509382, which is located at 11q14.3, the mutual translocation region of the famous DISC1 translocation [t (1; 11) (p42.1; q14.3)]. METHODS: We genotyped eleven single-neucleotide polymorphism (SNPs) within or related to DISC1 (rs821597, rs821616, rs4658971, rs1538979, rs843979, rs2812385, rs1407599, rs4658890, and rs2509382) using the PCR-RFLP methods. RESULTS: In all, there were 575 participants (225 schizophrenic patients and 350 healthy controls) of either Malay or Chinese ethnicity. The case-control analyses found two SNPs that were associated with schizophrenia [rs4658971 (p=0.030; OR=1.43 (1.35-1.99) and rs1538979-(p=0.036; OR=1.35 (1.02-1.80)] and rs2509382-susceptibility among the males schizophrenics [p=0.0082; OR=2.16 (1.22-3.81)]. This is similar to the meta-analysis findings for the Caucasian populations. CONCLUSION: The study supports the notion that the DISC1 gene is a marker of schizophrenia susceptibility and that rs2509382 in the mutual DISC1 translocation region is a susceptibility marker for schizophrenia among males in Malaysia. However, the finding of the study is limited due to possible genetic stratification and the small sample size.